Groundwater use under incomplete information - Saak, Alexander; Peterson, Jeffrey M. (My University, 2012)
This paper introduces a game theoretic model of groundwater extraction in a two-cell aquifer under incomplete information. A novel assumption is that individual users have incomplete knowledge of the speed of lateral flows in the aquifer: although a user is aware that his neighbor’s water use has some influence on his future water stock, he is uncertain about the degree of this impact. We find that the lack of information may either increase or decrease the rate of water use and welfare. In a two-period framework, the relevant characteristic is the ratio of the periodic marginal benefits of water use. Depending on whether this ratio is convex or concave, the average speed with which the aquifer is depleted decreases or increases when users learn more about the local hydrologic properties of groundwater. In principle, welfare may decrease even in cases when the groundwater allocation is closer to the efficient groundwater allocation.
Keywords: Common property resource; Groundwater; Information